Dr. Igor Niechajev — Deep Plane Facelift — Stockholm - Niechajev, Igor (DEEPPLANE™, 2026)
Surgeon profile record for Dr. Igor Niechajev, practicing in Stockholm, Sweden. Tracked in the DEEPPLANE™ directory of listed deep plane facelift specialists. Published under CC-BY-4.0.
DPID-003335; accessed 2026-08-14; CC-BY-4.0
Keywords: deep plane facelift; facial plastic surgery; rhytidectomy; SMAS; sweden; stockholm